2009
DOI: 10.1111/j.1440-1797.2009.01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Bone density in patients with chronic kidney disease stages 4‐5

Abstract: SUMMARY:Skeletal fractures are common in dialysis patients. Bone density measurements predict fractures in the general population, but in patients with chronic kidney disease (CKD) there is limited ability to predict fractures with these techniques. A review of the literature in patients with CKD stage 5 shows that bone density in the cortical bone of the radius or hip is generally lower compared with normal reference ranges by about one to two standard deviations, whereas in the spine bone density tends to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 93 publications
2
27
1
Order By: Relevance
“…Ott 15 has examined the results from studies that measure BMD and serum PTH in CKD patients and has observed that none of these studies found a positive relationship between PTH and BMD; either the relationship was not significant or there was a significant inverse correlation. Similarly, we also did not find an association between BMD and apelin.…”
Section: Discussionmentioning
confidence: 99%
“…Ott 15 has examined the results from studies that measure BMD and serum PTH in CKD patients and has observed that none of these studies found a positive relationship between PTH and BMD; either the relationship was not significant or there was a significant inverse correlation. Similarly, we also did not find an association between BMD and apelin.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some patients have a minimal bone loss, others show rapid bone losses 86. Additionally, the presence of aorta calcification and spinal osteoarthritis may bias BMD measurement,88 being the hip and the radius better sites for the BMD assessment. Interestingly, it has been shown in a population of 2754 elderly subjects, including 587 subjects with CKD, that lower BMD was a risk factor associated with skeletal fractures 89.…”
Section: Bone and Musculoskeletal Abnormalities In Chronic Kidney Dismentioning
confidence: 99%
“…Any calcium in the path of the X-ray beam will contribute to the BMD measurement (degenerative disc disease, osteophytes, osteoarthritis with hyperostosis, aortic calcifications, etc.) and cause false elevation 3,[16][17][18] . Lower BMD and higher prevalence of T-score values corresponding to osteoporosis in females in this study are consistent with data in the general population 19,20 .…”
Section: Both Gender Females Malesmentioning
confidence: 99%